Perlindungan Hukum Terhadap Konsumen Indihome Ditinjau Dari Undang-Undang Perlindungan Konsumen - Raka Wicaksono; Andriyanto Adhi Nugroho; Rosalia Dika Agustanti (Jurnal Ilmiah Penegakan Hukum, 2021)
This study aims to determine the legal protection for consumers of Indihome internet services who feel they have been harmed by the services provided by Indihome, then further discuss the liability of PT. Telekomunikasi Indonesia as a provider of Internet services to consumers who have sued the problem. This study uses a normative juridical method with a law approach, a case approach and a conceptual approach, with primary and secondary legal sources. The results of the study show that legal protection for consumers also includes consumer rights as regulated in Article 4 of Law Number 8 of 1999 and Article 45 of Law Number 8 of 1999. There are obstacles to damage or losses experienced by consumers related to the quality of services provided is the responsibility of PT. Telecommunications Indonesia as a business actor. In addition to demanding rights, consumers must also pay attention to their obligations such as reading or following information instructions and procedures for the use or utilization of goods and/or services, for the sake of security and safety which aims to prevent consumers from things that will harm consumers later. The form of responsibility of PT. Telekomunikasi Indonesia that is given to IndiHome consumers, namely providing compensation according to company regulations, providing compensation, resolving disputes regarding the implementation and/or interpretation of subscription contracts, are jointly resolved by PT. Telekomunikasi Indonesia and customers by deliberation